All Days 2010
DOI: 10.2118/136941-ms
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Response of Carbonate Core-Plugs – Influence of Heterogeneous Rock Properties on Permittivity

Abstract: Heterogeneities of carbonate core plugs can be assessed by different measurements resulting in different interpretations. In this study, dielectric spectroscopy, NMR, and tracer displacement method performed on the same cores reflect different aspects of heterogeneity related to their own characteristic length scales and physics of the measurements, which complement each other in a multiphysical interpretation. The complex dielectric permittivity measured on carbonate core samples in the reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…In particular, Yoshikawa and Overduin (2005) and Watanabe and Wake (2009) studied the freezing characteristics in various saturated and unsaturated soils above and below 0° C, measuring the liquid water content and relative permittivity with NMR and TDR techniques. Zhang et al (2010) and Clennel et al (2007) found that the liquid water content estimated using the expanded mixing model is in agreement with the values measured by NMR for different soil types, water and ice content and temperature.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…In particular, Yoshikawa and Overduin (2005) and Watanabe and Wake (2009) studied the freezing characteristics in various saturated and unsaturated soils above and below 0° C, measuring the liquid water content and relative permittivity with NMR and TDR techniques. Zhang et al (2010) and Clennel et al (2007) found that the liquid water content estimated using the expanded mixing model is in agreement with the values measured by NMR for different soil types, water and ice content and temperature.…”
Section: Introductionsupporting
confidence: 64%
“…Zhang et al . () and Clennel et al . () found that the liquid water content estimated using the expanded mixing model is in agreement with the values measured by NMR for different soil types, water and ice content and temperature.…”
Section: Introductionmentioning
confidence: 93%